Effects of formulation types on pharmacodynamics of warfarin in patients with cerebral infarction and dysphagia - Kim YJ; Jeong JW; Song Y; Koo TS (Clinical Pharmacology: Advances and Applications, 2019)
Young-Ji Kim,1,2 Jong-Woo Jeong,1 Youngshin Song,3 Tae-Sung Koo1 1Graduate School of New Drug Discovey and Development, Chungnam National University, Daejeon 305-764, Republic of Korea; 2Chungnam National University Hospital, Daejeon 305-764, Republic of Korea; 3Department of Nursing, College of Nursing, Chungnam National University, Daejeon 305-764, Republic of Korea Purpose: The purpose of this study was to investigate the effects of the type of formulation on the efficacy of warfarin. Materials and methods: The electronic medical records of patients with cerebral infarction, who were administered tablet or powder formulations of warfarin from 2013–2015, were retrospectively analyzed. Clinical data, changes in the international normalized ratio (INR), the warfarin dose, and the time to reach the plasma warfarin concentration that could induce an adverse effect, such as bleeding, were evaluated. Coefficients of variation of INR and of the warfarin dose, as well as the warfarin sensitivity index (WSI), were used to evaluate the INR stability. Statistical analysis of the data was performed using a independent t-test. Additionally, survival analysis was performed. Results: The data showed that 57 and 137 patients were administered warfarin as powder and tablet formulations, respectively. We noted that INR, WSI, and INR/dose × body weight differed significantly between the two groups of patients. The median survival times to reach the plasma warfarin concentration that could induce adverse effects were 3.6 and 4.2 days of treatment with the powder and tablet formulations, respectively. The efficacy of warfarin was higher when the drug was administered as a powder than when it was administered as a tablet. Conclusion: The findings of this study indicate that INR should be carefully monitored in the first 4 days of warfarin administration as a powder formulation. Keywords: warfarin, pharmacodynamic, dysphagia, survival analysis